2020
DOI: 10.1093/insilicoplants/diaa006
|View full text |Cite
|
Sign up to set email alerts
|

A new tool for discovering transcriptional regulators of co-expressed genes predicts gene regulatory networks that mediate ethylene-controlled root development

Abstract: Gene regulatory networks (GRNs) are defined by a cascade of transcriptional events by which signals, such as hormones or environmental cues, change development. To understand these networks, it is necessary to link specific transcription factors (TFs) to the downstream gene targets whose expression they regulate. Although multiple methods provide information on the targets of a single TF, moving from groups of co-expressed genes to the TF that controls them is more difficult. To facilitate this bottom-up appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 72 publications
0
12
0
Order By: Relevance
“…Using AgriGo v2.0, we looked for enriched function in these groups, finding that six out of seven PaLD groups were enriched in gene ontology annotations. We used TF DEACoN [23], which looks for significant enrichment in genes that have been shown to be targets of TFs defined by a publicly available DNA Affinity Purification (DAP)-Seq data set [24]. This analysis revealed that 5 out of 7 groups were enriched in targets of known TFs.…”
Section: Enrichment Analysis and Conserved Tf Binding In A Pald-gener...mentioning
confidence: 99%
“…Using AgriGo v2.0, we looked for enriched function in these groups, finding that six out of seven PaLD groups were enriched in gene ontology annotations. We used TF DEACoN [23], which looks for significant enrichment in genes that have been shown to be targets of TFs defined by a publicly available DNA Affinity Purification (DAP)-Seq data set [24]. This analysis revealed that 5 out of 7 groups were enriched in targets of known TFs.…”
Section: Enrichment Analysis and Conserved Tf Binding In A Pald-gener...mentioning
confidence: 99%
“…The performed AthaMap analysis [38] of the promoter regions of the genes encoding TAA1, TAR1, and TAR2 identified the consistent presence of motifs for APETALA2/Ethyleneresponsive element binding proteins (AP2/ERBP), among which were Ethylene Response Factor 1 (ERF1), Ethylene Response Factor 2 (ERF2), Ethylene-Insensitive3-Like (TEIL), Target of Early Activation Tagged 1 /2 (TOE1/2), and EIN3 (Figure S1). The ethylene regulatory link to local auxin biosynthesis was also assessed by the TF DEACoN (Transcription Factor Discovery by Enrichment Analysis of Co-expression Networks) tool [47] which uses Arabidopsis DNA affinity purification sequencing (DAP-Seq) data to make predictions about which TFs may be involved in transcriptional responses of co-regulated genes.…”
Section: Constitutive Mutant Ctr1-1 Has Increased Local Auxin Biosynthesismentioning
confidence: 99%
“…were Ethylene Response Factor 1 (ERF1), Ethylene Response Factor 2 (ERF2), Ethylene-Insensitive3-Like (TEIL), Target of Early Activation Tagged 1 /2 (TOE1/2), and EIN3 (Figure S1). The ethylene regulatory link to local auxin biosynthesis was also assessed by the TF DEACoN (Transcription Factor Discovery by Enrichment Analysis of Co-expression Networks) tool [47] which uses Arabidopsis DNA affinity purification sequencing (DAP-Seq) data to make predictions about which TFs may be involved in transcriptional responses of co-regulated genes. TF DEACoN analysis of the genes encoding enzymes from the Tryptophan-dependent auxin biosynthesis (TAA1, TAR1, TAR2, YUC1-11) identified three AP2-EREBP transcription factors (RAP2.1, RAP2.9, and TINY or also known as ERF040) with fourfold enrichment of targets (Table S1).…”
Section: Constitutive Mutant Ctr1-1 Has Increased Local Auxin Biosynthesismentioning
confidence: 99%
See 2 more Smart Citations